2017
DOI: 10.1016/j.conb.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Architecting the myelin landscape

Abstract: Myelin increases the speed and efficiency of action potential propagation. Yet, not all axons are myelinated and some axons are discontinuously myelinated, prompting the question of how myelinating glia select axons for myelination. Whereas myelination by Schwann cells depends on axonal induction, oligodendrocytes can form myelin membrane in the absence of axons. However, oligodendrocytes alone cannot architect the complex myelination patterns of the central nervous system and recent advances have implicated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 60 publications
(89 reference statements)
1
33
0
1
Order By: Relevance
“…Many neuronal factors influence oligodendrocyte development and myelination, but to date, no single neuronal factor has been identified as necessary to initiate and form myelin sheaths. Although it is possible that such factors will be identified by future studies, an alternative possibility is that oligodendrocytes will initiate wrapping and myelination of any candidate target axon that possesses a supra-threshold axon diameter (> 0.3 µm) and lacks inhibitory signals [17,22], reviewed by [9,13,14]. Our studies do not directly address or exclude this possibility, and it will be important for future studies to determine if the transition from oligodendrocyte-axon contact to initial wrapping is influenced by axonal signals, or is solely mediated by an oligodendrocyte-intrinsic program in vivo.…”
Section: Axonal Influence On Oligodendrocyte Behavior During Initial mentioning
confidence: 99%
See 3 more Smart Citations
“…Many neuronal factors influence oligodendrocyte development and myelination, but to date, no single neuronal factor has been identified as necessary to initiate and form myelin sheaths. Although it is possible that such factors will be identified by future studies, an alternative possibility is that oligodendrocytes will initiate wrapping and myelination of any candidate target axon that possesses a supra-threshold axon diameter (> 0.3 µm) and lacks inhibitory signals [17,22], reviewed by [9,13,14]. Our studies do not directly address or exclude this possibility, and it will be important for future studies to determine if the transition from oligodendrocyte-axon contact to initial wrapping is influenced by axonal signals, or is solely mediated by an oligodendrocyte-intrinsic program in vivo.…”
Section: Axonal Influence On Oligodendrocyte Behavior During Initial mentioning
confidence: 99%
“…For example, emerging evidence indicates that axonal galectins mark non-myelinated axon segments, and that galectins may be mis-expressed within Multiple Sclerosis lesions [43,44]. Numerous additional negative regulators of myelination have been identified that if targeted, could mitigate the barriers to remyelination (reviewed by [9,13,14]). It will be interesting for future studies to identify spinal cord commissural axon properties responsible for the superior sheath stabilizing and growth inducing properties of this subtype in comparison to reticulospinal and spinal sensory axons.…”
Section: Implications For Myelin Plasticity and Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells are tiled and maintain a tightly regulated resident population by balancing self-renewal, apoptosis, and oligodendrocyte differentiation (Barres et al, 1992;Hill, Patel, Goncalves, Grutzendler, & Nishiyama, 2014;Hughes, Kang, Fukaya, & Bergles, 2013;Trapp, Nishiyama, Cheng, & Macklin, 1997). Much is known about the molecular cues that induce oligodendrocyte differentiation from NG2 glia (reviewed in Nishiyama, 2007;Emery, 2010;Liu & Casaccia, 2010;Zuchero & Barres, 2013); however, less is known about the mechanisms inducing myelination of some axons and not others and some axonal segments and not others, in specific patterns at discrete time points (Almeida & Lyons, 2017;Osso & Chan, 2017).…”
Section: Introductionmentioning
confidence: 99%